A Large-Scale Multiple Genome Comparison of Acidophilic Archaea (pH ≤ 5.0) Extends Our Understanding of Oxidative Stress Responses in Polyextreme Environments - Gonzalo Neira; Eva Vergara; Diego Cortez; David S. Holmes (Antioxidants, 2021)
Acidophilic archaea thrive in anaerobic and aerobic low pH environments (pH < 5) rich in dissolved heavy metals that exacerbate stress caused by the production of reactive oxygen species (ROS) such as hydrogen peroxide (H2O2), hydroxyl radical (·OH) and superoxide (O2−). ROS react with lipids, proteins and nucleic acids causing oxidative stress and damage that can lead to cell death. Herein, genes and mechanisms potentially involved in ROS mitigation are predicted in over 200 genomes of acidophilic archaea with sequenced genomes. These organisms are often be subjected to simultaneous multiple stresses such as high temperature, high salinity, low pH and high heavy metal loads. Some of the topics addressed include: (1) the phylogenomic distribution of these genes and what this can tell us about the evolution of these mechanisms in acidophilic archaea; (2) key differences in genes and mechanisms used by acidophilic versus non-acidophilic archaea and between acidophilic archaea and acidophilic bacteria and (3) how comparative genomic analysis predicts novel genes or pathways involved in oxidative stress responses in archaea and likely horizontal gene transfer (HGT) events.